Development of Project Management Competencies among Members of the Roma Community - Rebeka D. VLAHOV GOLOMEJIC; Rok PETJE (Communications of International Proceedings, 2022)
The Roma community is the largest transnational minority in Europe, yet its people are still often socially and racially discriminated against. Recently, this issue was recognized by the European Union and many of its member countries. In Slovenia, the community is defined as having particular ethnic and cultural characteristics, but problems like social exclusion, insufficient education and high unemployment still persist. Therefore, the Romano Kher project was designed and conducted in three phases to address these issues, whilst creating new opportunities for people of the Roma community in Pomurje region. In this paper, quantitative and qualitative research were undertaken to analyze project results through phases. The first phase (2011–2014) included training the members of the Roma community in the field of project preparation and implementation. In the second phase (2014–2019), the Association for the development of the Roma community was established and completed 30 projects for more than 20 organizations, making it one of the most important organizations for implementation of Roma projects, thusly laying foundations for the third phase (2021-2026) which will include establishing the Project Office for Roma Community Development within the Regional Development Agency in Pomurje, formalizing project management training and competence assessment for the Roma community, and expanding project activities to Central and South-Eastern Europe.
Keywords: project management competencies; projects; project management; Roma community